Análise da resposta dinâmica de um modelo em escala reduzida de plataforma offshore do tipo T.L.P. - Andrade, Ricardo Franklin Mendes de (1989)
Experimental tests performed on a hydroelastic reduced scale model of a Tension Leg Platform for deep water are reported. Comparisons between theoretical responses obtained with a simplified 6 D.O.F. are made. Among the experimental results, those related to damping ratio, inertia and drag coefficients should be highlighted. Tests were performed to verify the contribution of the deck mass distribution for the model natural periods. The experimental time responses from tests under impacts and under wave action with different incident angles are reported. Experiments performed on the reduced sclae model have allowed calibration of numerical models as well as the observation of relevant effects that arise from fluid-structure interaction. Finally, it is important to emphasize the construction of small scale models for the determination of experimental parameters and for the calibration of numerical models to be used in designing this type of offshore platforms.